Drought responsiveness in six wheat genotypes: identification of stress resistance indicators - Guizani, Asma; Askri, Hend; Amenta, Maria Laura; Defez, Roberto; Babay, Elyes; Bianco, Carmen; Rapaná, Nicoletta; Finetti-Sialer, Mariella; Gharbi, Fatma (Frontiers in Plant Science, 2023)
Wheat (Triticum aestivum L.) is among the world's most important staple food crops. In the current climate change scenario, a better elucidation of wheat response mechanisms to water stress could help promote its productivity in arid ecosystems. In this study, water relations, gas exchange, membrane integrity and agronomic traits were evaluated in six drought-stressed wheat genotypes (D117, Syndiouk, Tunisian durum7, Utique, Mahmoudi AG3 and BT) as compared to well-watered ones. Although drought altered leaf area, chlorophyll content, stomatal density, photosynthetic rate and water-use efficiency in all plants, their relative water content at turgor loss point (RWC0) was maintained. Changes in osmotic potential at turgor loss point (Ψπ 0 ), the bulk modulus of elasticity (Ɛmax) and stringency of stomatal regulation differed greatly between the studied genotypes. For the drought-sensitive genotypes AG3 and BT, no significant changes were observed in Ψπ 0 , whereas the stomatal conductance (gs) and transpiration rate (E) were reduced after stress as compared to wellwatered conditions. After stress, these varieties avoided turgor loss through an accurate stomatal control, which led to a remarkable decline in yield components. On the contrary, for Syndiouk, D117, Codice campo modificato ha eliminato: 4 35 ha eliminato: During drought